2019
DOI: 10.18637/jss.v091.i01
|View full text |Cite
|
Sign up to set email alerts
|

dbscan: Fast Density-Based Clustering with R

Abstract: This article describes the implementation and use of the R package dbscan, which provides complete and fast implementations of the popular density-based clustering algorithm DBSCAN and the augmented ordering algorithm OPTICS. Package dbscan uses advanced open-source spatial indexing data structures implemented in C++ to speed up computation. An important advantage of this implementation is that it is up-to-date with several improvements that have been added since the original algorithms were publications (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
308
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 537 publications
(370 citation statements)
references
References 48 publications
0
308
0
5
Order By: Relevance
“…In our experiments, we found that accurate detection could be performed even clustering a small number of points. The recommended number for DBSCAN's MinPts parameter is one more than the number of dimensions [23]. In our case, the number of dimensions is two − the interrupts over context switches ratio and the time.…”
Section: A Real-time Anomaly Detectionmentioning
confidence: 92%
“…In our experiments, we found that accurate detection could be performed even clustering a small number of points. The recommended number for DBSCAN's MinPts parameter is one more than the number of dimensions [23]. In our case, the number of dimensions is two − the interrupts over context switches ratio and the time.…”
Section: A Real-time Anomaly Detectionmentioning
confidence: 92%
“…First, dimension reduction was executed on a combined data table of TSS normalized OTUs and ARGs and MGEs using t-SNE algorithm (29) and the R package Rtsne (55), with 50,000 iterations and “perplexity” set to 5. Then, clusters in the two-dimensional data were identified using HDBSCAN algorithm (30) in the package dbscan (56). The minimum number of members in clusters (“minPts”) was set to 3.…”
Section: Methodsmentioning
confidence: 99%
“…PCA on sRNAgenerating loci was performed in R with "FactoMineR" v1.42 (Lê et al, 2008) and "factoextra" v1.0.5 1 packages. HDBSCAN clustering was performed (parameters: minPts = 20) with dbscan R package v1.1-4 (Hahsler et al, 2019). Homology analysis of G. margarita-(Gma)-sRNA-generating loci with fungal repetitive elements from RepBase 23.04 2 was performed with tblastx (Evalue ≤ 0.00005) (Camacho et al, 2009).…”
Section: Bioinformatics Pipelinementioning
confidence: 99%